Traditional and Commercial Herb Use in Health Self-Management among Rural Multiethnic Older Adults - Altizer, Kathryn (2011)
This study analyzes the role of traditional and commercial herbs in older adults’ health self-management based on Leventhal’s Self-Regulatory Model conceptual framework. Sixty-two African American and white adults age 65 and older completed qualitative interviews describing the forms of herbs currently being used, sources of information about them, interpretations of health (acute symptoms or chronic conditions) that lead to their use, and the initiation and suspension of use. Traditional herbs are native to the region or have been traditionally cultivated; usually taken raw or boiled to produce tea; and used for treating mild symptoms. Commercial herbs are prepared as pills, extracts, or teas; they are purchased at local stores or ordered by catalog or internet; and used for health promotion, illness prevention or treatment of chronic conditions. Herbs are widely used among older adults; this analysis differentiates the types of herbs they use and their reasons for herbs use.